Molecular and Pathological Characterization of Velogenic Newcastle Disease Virus Causing Late Embryonic Death in Ostrich (Struthio camelus) in Egypt - Ghaly, Samar; Eladl, Abdelfattah; Abdeen, Shaker; Elshaieb, Ahmed (Journal of Advanced Veterinary Research, 2023)
In Egypt, ostrich farming has had a great increase during the last few years. The most common problems facing ostrich farmers are a high percentage of late embryonic mortality and low hatchability. This study was designed to survey the main causes of late in-shell ostrich embryonic death. A total of 100 freshly dead shell ostrich embryos, all of them were in the second half of the incubation period with different ages ranging from 25 to 39 days old, were received during the breeding seasons of the period from October 2018- October 2021, from different ostrich farms in Egypt, suffered from late-stage embryonic death during artificial incubation, respiratory signs and diarrhea in breeders, moreover, the surveyed ostrich farms were near to chicken farms suffered from Newcastle Disease outbreaks. Gross findings in all embryos were recorded as anasarca, severe general congestion, and hemorrhages. In this study, 66 dead shell ostrich embryos out of 100 (66%) were immunohistochemically positive for Newcastle Disease Virus. Four Velogenic Newcastle Disease Virus strains (genotype VIIb) were molecularly characterized in 4 immune-positive ND embryos (from 4 different ostrich farms in 4 different Egyptian governorates) by RT-PCR and F gene sequencing. In addition, all embryos were negative for bacterial isolation except for one vNDV positive embryo (1%) (25 days old) that was superinfected by Citrobacter spp. The main histopathological lesions of vNDV-positive ostrich embryos were general edema, extensive congested blood vessels, hemorrhages, necrosis, syncytial cells formation in the upper respiratory tract, and leukocytic cells infiltrations. To the best of our knowledge, this study is the first report of the Velogenic Newcastle Disease Virus that immunohistochemically and molecularly characterized dead ostrich embryos in Egypt, therefore, Newcastle Disease Virus vaccination of ostrich breeders is strongly recommended.